2017
DOI: 10.3389/fenvs.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in the Environment: Perspectives on in Vivo Terrestrial Toxicity Testing

Abstract: Over the last decade, engineered nanomaterials (NMs) brought a revolutionary development in many sectors of human life including electronics, paints, textiles, food, agriculture, and health care. However, the exponential growth in the number of NMs applications resulted in uncertainties regarding their environmental impacts. Currently, the common approach for assessing the toxicity of NMs such as, carbon-(fullerenes, single-and multi-walled carbon nanotubes), mineral-(gold and silver nanoparticles, cerium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…With the use of CNTs becoming more widespread, the amount of CNTs released into the environment is expected to increase, either accidentally or as waste, raising concerns about their impact on human health and ecosystems. Recent studies have reported that some CNTs exhibit toxicity to plants, animals, and microorganisms (Chen et al, 2015b;Kumarathasan et al, 2015;Hatami, 2017;Mendonca et al, 2017;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the use of CNTs becoming more widespread, the amount of CNTs released into the environment is expected to increase, either accidentally or as waste, raising concerns about their impact on human health and ecosystems. Recent studies have reported that some CNTs exhibit toxicity to plants, animals, and microorganisms (Chen et al, 2015b;Kumarathasan et al, 2015;Hatami, 2017;Mendonca et al, 2017;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans, it was found that proteins involved in oxidative stress protection and metal elimination, such as SOD isoforms, metallothioneins and heat shock proteins, have a key role in resistance to TiO 2 NPs. These NPs led to a substantial decrease in both head thrash or body bend in nematode mutants (SOD-2, SOD-3, metallothionein-2 and heat shock protein-16.48) compared to the wild type [136].…”
Section: Titanium Nanomaterialsmentioning
confidence: 96%
“…Cadmium telluride quantum dots (CdTe QDs) caused abnormal foraging behavior (related to the altered function of the motor neurons) in C. elegans, at long-term early onset exposure. Thus, a decrease in fluorescence of the motor neurons cell bodies was observed, indicating an alteration in their development [136]. The main route of exposure of nematodes to QDs was determined, by fluorescence microscopy, to be through the digestive tracts [150].…”
Section: Cadmium Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CNTs are needle-like, similar to asbestos, and can induce mesothelioma, pleural fibrosis, and lung cancer ( Donaldson et al, 2013 ). Recent studies have reported that some CNTs are also toxic to plants, animals, and microorganisms, and may alter biodiversity ( Chen et al, 2017 ; Mendonca et al, 2017 ; Chen et al, 2018 ; Kong et al, 2023 ); Such CNTs cause growth inhibition and reduced seed germination in plants ( Begum and Fugetsu, 2012 ; Hatami, 2017 ), embryo growth inhibition and pneumonia in animals ( Roman et al, 2013 ; Al Moustafa et al, 2016 ; Fujita et al, 2016 ), and cell membrane damage in microorganisms ( Liu et al, 2009 ; Yadav et al, 2016 ). As the use of CNTs has become more widespread, the amount of CNTs released into the environment, either accidentally or as waste, may also increase, leading to additional concerns.…”
Section: Introductionmentioning
confidence: 99%